A new high-resolution palaeotemperature record during the Middle–Late Ordovician transition derived from conodont δ18O palaeothermometry. Issue 4 (2022) - Liu, Kang; Jiang, Maosheng; Zhang, Liyu; Chen, Daizhao
No abstract available